AMELOBLASTOMA OF THE JAW BONES: CLINICAL STUDY AND CASE REPORT - Simeon Dimanov; Yanko Yankov; Lyuben Stoev (Peytchinski Publishing, 2023)
Ameloblastoma's origin is the epithelium of ectodermal origin, which means they are tumors arising from the cells around the tooth root or, in close approximation, derived from the ectoderm. It is a benign but locally aggressive tumor with a high tendency to recur. Patients after ameloblastoma treatment need a life-long follow-up. We present an 82-year-old female patient diagnosed with ameloblastoma and treated by us. She has been referred to the clinic by doctor of dental medicine because of a routine panoramic rentgenography, which displayed rentgenographic evidence for a cyst-like tumor formation on her mandible. The patient did not have any complaints. The patient was reffered for further paraclinical imaging tests - dental panoramic radiography (OPG) and cone beam computed tomography (CBCT). The location and borders of the lesion were determined - it was circumferentially attached to the root of 44 tooth, well-outlined linea albuginea was present, the diameter of the lesion was approximately 26 mm. Bone curettage was the treatment plan - the surgical intervention in this volume was chosen as a consequence of the refusal of the patient of a partial mandibulectomy and according to her age - 82. The histopathological examination of the curettage revealed a locally infiltrative tumor process engaging the submitted bone and fibrous tissue. The final pathological diagnosis was conventional ameloblastoma with a predominantcanthomatous pattern. On the control panoramic rentgenography one year after the operation, no pathological changes in the field of the operative site were found.